JP5318855B (2013)
The present invention relates to a method of characterizing lung function in a subject in need of such characterization. The method comprises performing an imaging technique, on a voxel defined within a lung space of interest. Image data is generated over a time period during which the subject inhales gases with at least two different partial pressures of a paramagnetic gas. A compartmental model algorithm is applied to the image data generated for the voxel to provide information on ventilation, diffusion and perfusion of a lung. The paramagnetic gas is preferably Oxygen. The imaging technique is preferably Oxygen Enhanced Magnetic Resonance Imaging (OE-MRI).